Respon Pertumbuhan Bibit Ylang-Ylang Terhadap Persaingan Rumput Signal dan PenambahaN NPK - Irdika Mansur; Ega Diany (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
The application of silvopasture between the ylang-ylang (Cananga odorata forma enuine) plant and the signal grass (Brachiaria decumbens) has the potential to produce large economic value. The purpose of this study was to determine the response of ylang-ylang seedling growth to competition with grass signals without or with the addition of NPK, and to find out the optimal dose of NPK fertilizer that could help the growth of ylang-ylang seeds planted with grass signals. This study was conducted using a factorial pattern in a complete randomized design with the first factor being planting signal grass and the second factor was adding NPK fertilizer. The results of this study indicate that planting signal grass and adding NPK as much as 0,75 g significantly affected to the growth of ylang-ylang seedlings. The presence of signal grass in the same media showed no inhibition of the growth of ylang-ylang seedlings. The addition of NPK with the dose used did not significantly affect the growth of ylang-ylang seeds. Keywords: Brachiaria decumbens, Cananga odorata, NPK fertilizer dosage, silvopasture